2008
DOI: 10.1159/000127317
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Tetanus Vaccination Status in Patients with Chronic Leg Ulcers

Abstract: Background: Tetanus disease is caused by Clostridium tetani and is one of the most common infectious diseases worldwide. Despite international recommendations for patients with a chronic leg ulcer, there has been a distinctive lack of protection provided by vaccination for these patients in the past decades. Methods: Within the context of our prospective clinical investigation we consecutively determined the concentrations of immunoglobulin G antibodies against C. tetani in 100 patients with a chronic leg ulce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…There are numerous studies in the literature concerning immunity rates against tetanus in various patient populations, but studies including patients suffering from DFW or chronic leg ulcers are very limited. Korber et al [5] reported that 47% of all patients suffering from chronic leg ulcers showed an insufficient tetanus antibody concentration, and their subanalysis revealed that 70% of patients aged over 80-year-old had insufficient protection against tetanus. In the present study, we found that sufficient protection rates in DFW patients decreased with increasing age, as in the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous studies in the literature concerning immunity rates against tetanus in various patient populations, but studies including patients suffering from DFW or chronic leg ulcers are very limited. Korber et al [5] reported that 47% of all patients suffering from chronic leg ulcers showed an insufficient tetanus antibody concentration, and their subanalysis revealed that 70% of patients aged over 80-year-old had insufficient protection against tetanus. In the present study, we found that sufficient protection rates in DFW patients decreased with increasing age, as in the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%
“…Gangrenous tissue is another factor that is frequently seen in DFWs and predisposes patients to tetanus [3,4] . Over 70% of all diagnosed tetanus infections occur in people over 50 years of age, and 11% of all tetanus cases were found in patients suffering from chronic wounds [5] .…”
Section: Introductionmentioning
confidence: 99%
“…16 Up to 47% of patients with chronic leg ulcers-which affect 3-5% of people over 65 17 -have insufficient IgG concentrations for immunity, rising to 70% in patients aged over 80. 9 Consequently, chronic ulcerated wounds should be considered as prone to tetanus, and recommendations highlight the importance of prophylaxis. 9 11 15 18 Tetanus after surgery is uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have assessed adult tetanus seroprotection rates (antitoxin levels of >0.1 or >0.15 IU/ml) in countries with comprehensive vaccination programmes: protective antitoxin levels were seen in 72% to 90% of patients in the USA,20 21 80% in England and Wales22 and 64% in Belgium 23. Of note was the observation that the degree of protection was lower in older people (31% to 60% in individuals >60 years20 21 22 23 24 in the USA, UK and Belgium), in women (64% to 86% in the US studies20 21) and in immigrants (52% to 75% in the US studies20 21 and 45% to 52% in the Belgian study23). …”
Section: Determining Tetanus Protection Statusmentioning
confidence: 99%